Hellraisers - Smith, Alexander Gordon, 1979- (Smith, Alexander Gordon, 1979- Devil's engine., 2015)
Marlow Green is a high school boy in New York who is always in trouble for vandalism and acting out, until one day he stumbles into the middle of a battle with a demon, and learns about The Devil's engine--an ancient machine which can grant anything you wish for, in exchange for your soul.